1992
DOI: 10.1111/j.2042-3306.1992.tb02808.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the risk of developing sarcoid tumours in horses

Abstract: Summary A retrospective case‐control study was conducted to identify risk factors in horses associated with the development of the common skin tumours known as sarcoids. The study involved 503 sarcoid cases diagnosed (January 1980‐December 1989) at New York State College of Veterinary Medicine and a similar number of controls (non‐sarcoid cases). Data on age, breed and sex of cases and controls were obtained from computerised records. Multiple logistic regression analysis was used to identify risk factors. Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
13

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 13 publications
3
37
0
13
Order By: Relevance
“…12 Alternatively, induction of equine sarcoids is a multifactorial process, and it is reasonable to suggest that some sarcoids may develop without BPV infection. 1,2,25 This study is the first to report that bovine papillomavirus DNA is present in equine spindle cell tumors in the skin other than sarcoids. Although previous studies reported that BPV was not associated with neoplasms in horses other than sarcoids, 10,13,28 those studies examined carcinomas, melanomas, cystadenocarcinomas, papillomas, hemangiomas, and lymphomas (ie, not other cutaneous spindle cell tumors).…”
Section: Discussionmentioning
confidence: 92%
“…12 Alternatively, induction of equine sarcoids is a multifactorial process, and it is reasonable to suggest that some sarcoids may develop without BPV infection. 1,2,25 This study is the first to report that bovine papillomavirus DNA is present in equine spindle cell tumors in the skin other than sarcoids. Although previous studies reported that BPV was not associated with neoplasms in horses other than sarcoids, 10,13,28 those studies examined carcinomas, melanomas, cystadenocarcinomas, papillomas, hemangiomas, and lymphomas (ie, not other cutaneous spindle cell tumors).…”
Section: Discussionmentioning
confidence: 92%
“…Evidence for a genetic basis of ES as an important intrinsic factor includes family- (Ragland et al 1966;James 1968;Stannard 1978) and breed-predispositions (Angelos et al 1988;Mohammed et al 1992), associations of ES with certain equine leukocyte antigen alleles (Meredith et al 1986;Brostr€ om et al 1988;Lazary et al 1994) and with other genomic loci (Jandova et al 2012). Furthermore, a recent segregation analysis of ES disease in a large sample of the FranchesMontagnes (FM) horse population revealed an estimated heritability of up to 21% (Christen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors remain equivocal, although MHC type, age and sex are emerging as worthy of greater scrutiny. On balance, it would appear that young males appear to be at more risk of disease (Mohammed et al, 1992;Reid et al, 1994;Torrontegui & Reid, 1994;Reid & Mohammed, 1997). Reid & Mohammed (1997) attempted to address the apparent paragenital predilection site for the tumour in young males, suggesting a possible association with castration.…”
Section: Epidemiologymentioning
confidence: 99%